Genetic structure of natural populations of Cedrelinga Cateniformis ‟tornillo” from the oriental region of Peru - Cruz, Wilbert (2020)
Tornillo is a forest species of wide distribution in the Peruvian Amazon, its irrational exploitation has generated losses in its diversity. Currently, there is no baseline for the development of conservation strategies due to limited knowledge of the structure genetic in tornillo populations which would allow the implementation of an adequate conservation program for the species. 91 individuals of the species were collected in five departments (Madre de Dios, Loreto, Puno, San Martín and Ucayali). The 5 most polymorphic RAPD primers were selected (OPA02, OPA04, OPA12, OPA18, and OPF05), identifying 96 polymorphic markers. The PIC ranged from 0.24 - 0.31; the AMP was 47.86%. No duplicates were reported. He between populations varied between 0.265 - 0.296; Madre de Dios presented a lower value (0.174). The Shannon index presented the same variation (0.402 - 0.447; 0.262). There is a spatial-genetic correlation (rxy = 0.311; p value < 0.001), specifically a genetic variability is found between departments (PhiPT = 0.256; p value < 0.0001). Loreto and Ucayali are genetically related. At the same time, San Martín and Puno have an origin in Ucayali (Masisea) and San Martín have an origin in Loreto (San Juan Bautista). These results will allow to initiate the bases of a conservation program for the sustainable use of the species.